Metal aerogel catalyst as well as preparation method and application thereof
By doping heteroatoms in metal aerogels, adjusting the electron structure of carbon material and the electron transport properties of the active metal center, a metal aerogel catalyst with uniform heteroatom distribution and controllable doping structure was prepared, which solved the problem of uneven distribution of heteroatoms and difficult-to-regulate forms in the prior art, and achieved efficient and highly selective catalytic performance.
Patent Information
- Application Number
- CN202411811947.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-12-29
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-10
AI Technical Summary
When preparing efficient and highly selective catalysts, the prior art faces the problems of uneven distribution of heteroatoms and difficult forms to regulate, especially during the pyrolysis process, heteroatoms tend to collapse and accumulate, affecting the catalytic performance.
By doping heteroatoms such as N, P, S, B and F in metal aerogels, adjusting the electronic structure of the carbon material and enhancing electron transport properties with the active metal center, a metal aerogel catalyst with a uniform heteroatom distribution and a controllable doping structure is prepared.
The activity and selectivity of the catalyst are improved, and excellent catalytic performance is shown in the hydrogenation reaction. By simply adjusting the type and amount of alkali in the hydrogel formation process, the regulation of material activity and selectivity is achieved.
Smart Images

Figure CN119633870A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysts, and in particular to a metal aerogel catalyst and a preparation method and application thereof. Background Art
[0002] Selective hydrogenation reaction refers to when two or more functional groups coexist in a substrate, or when different unsaturated substrates exist in the catalytic system, one of the functional groups or substrates is preferentially converted, while the other functional groups or substrates remain unchanged. In the field of fine chemicals, when the substrate contains multiple functional groups, it is necessary to selectively reduce the target functional group while keeping the other functional groups unchanged in order to synthesize flavors, pesticides, medicines, etc. Therefore, both bulk chemicals and fine chemicals production require efficient selective hydrogenation conversion, and the key lies in the preparation of efficient and highly selective catalysts.
[0003] Carbon materials have attracted extensive attention due to their excellent cost-effectiveness and outstanding stability. However, due to the lack of sufficient active sites, carbon materials often show low catalytic activity in hydrogenation reactions. Therefore, heteroatoms (e.g., N, B, P, and S) can be doped into the carbon matrix to adjust its electronic structure. Although the doping of heteroatoms itself has many advantages, they are prone to collapse and accumulation during pyrolysis, which will have an adverse effect on the catalytic performance. Transition metals (e.g., Fe, Co, and Ni) have been shown to play an important role in selective hydrogenation.
[0004] Many research teams at home and abroad have carried out research on heteroatom-doped carbon-coated metal materials. Patent CN116826024A discloses a doped porous hard carbon composite material, which achieves heteroatom doping by adding nitrogen and / or phosphorus-containing melamine, phosphoric acid, urea and pyrrole during the carbonization process. This method of adding an external dopant has a wide range of applications. Both metal and non-metal dopants can be used to prepare such materials (CN116854150A), which is the most commonly used heteroatom doping method. However, doping by simple blending may lead to uneven distribution of heteroatoms, and the heteroatom content and existence form are not easy to control. Therefore, there are also patent reports that the corresponding heteroatom-doped carbon materials are obtained by accurately synthesizing precursors containing heteroatoms and then carbonizing them. Patent CN116715327A discloses a N, P and B co-doped carbon material. They obtained a well-defined organic polymer by a fixed-point reaction of hexachlorocyclotriphosphazene with phenyldiboronic acid, and then calcined at a constant temperature of 750°C to obtain a heteroatom-doped carbon material. The heteroatoms in the material are evenly distributed and the doping structure is easy to control. However, such methods often require complex organic synthesis reactions, especially organic compounds containing P and B are often extremely sensitive, unstable and costly, which increases the difficulty of material synthesis and application. Therefore, it is still necessary to develop a simple and efficient heteroatom doping method to achieve uniform distribution and controllable regulation of a series of heteroatoms. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a metal aerogel catalyst and a preparation method and application thereof. The present invention utilizes the modification of carbon materials by heteroatoms and the enhanced electron transport properties with active metal centers to improve the activity of the metal aerogel catalyst. At the same time, the type and content of heteroatoms are controlled to adjust the catalytic microstructure of the active metal center, thereby improving the selectivity of the metal aerogel catalyst in the hydrogenation reaction.
[0006] In a first aspect, the present invention provides a metal aerogel catalyst, comprising a metal aerogel and heteroatoms doped in the metal aerogel; the metal aerogel comprises a metal and a carbon material coated on the metal; optionally, the carbon material contains N; wherein the metal is selected from one or more of Ni, Co, Mn, Cu or Fe; and the heteroatoms are selected from one or more of N, P, S, B or F.
[0007] Doping heteroatoms (e.g., N, B, P, and S) into a carbon matrix can adjust its electronic structure. Specifically, N doping will produce more carbon charge sites (C+), and the presence of such active sites will greatly promote substrate adsorption and ultimately enhance catalytic activity. In addition, P embedded in the carbon substrate has a strong electron-donating ability, which can cause a high degree of deformation of the carbon substrate, thereby generating enough vacancies and defects, which, on the one hand, facilitates the substrate to approach the metal active center, and on the other hand, controls the approach of the substrate by introducing pores, thereby further selectively converting.
[0008] In some embodiments, the heteroatom is selected from S and / or P.
[0009] In some embodiments, the total amount of the heteroatoms and N in the carbon material accounts for 0.5-15% of the mass of the metal aerogel catalyst, for example, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% or any value therebetween.
[0010] In some embodiments, the heteroatom accounts for 0.5-6% of the mass of the metal aerogel catalyst; for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 5%, 6% or any value therebetween.
[0011] In some embodiments, the total amount of N in the carbon material accounts for 1-10% of the mass of the metal aerogel catalyst; for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or any value therebetween.
[0012] In some embodiments, the metal accounts for 1-10% of the mass of the metal aerogel catalyst; for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or any value therebetween.
[0013] In some embodiments, when the heteroatom is P, the heteroatom accounts for 0.5-1.5% of the mass of the metal aerogel catalyst.
[0014] In some embodiments, the carbon material includes a carbon-containing substance formed by calcining biomass polysaccharides; preferably, the biomass polysaccharides are selected from one or more of chitosan, sodium alginate, glucose, bacterial cellulose, agarose or hyaluronic acid.
[0015] In a second aspect, the present invention provides a method for preparing a metal aerogel catalyst, comprising the following steps:
[0016] (1) mixing an acidic aqueous solution containing biomass polysaccharides, a metal salt aqueous solution and an alkaline solution containing heteroatoms to form a hydrogel;
[0017] (2) calcining the hydrogel to obtain a metal aerogel catalyst.
[0018] In some embodiments, the method for preparing the hydrogel comprises:
[0019] S1, mixing an acidic aqueous solution containing biomass polysaccharides with an aqueous solution of metal salts to obtain a biomass polysaccharide-metal complex solution;
[0020] S2, adding an alkali solution containing heteroatoms dropwise into the polysaccharide-metal complex solution to obtain a hydrogel.
[0021] In some embodiments, the biomass polysaccharide is selected from one or more of chitosan, sodium alginate, glucose, bacterial cellulose, agarose or hyaluronic acid. In some embodiments, the acidic aqueous solution is selected from one or more of formic acid aqueous solution, acetic acid aqueous solution, propionic acid aqueous solution, hydrochloric acid aqueous solution, sulfuric acid aqueous solution, phosphoric acid aqueous solution or nitric acid aqueous solution.
[0022] In some embodiments, the acidic aqueous solution containing biomass polysaccharides is chitosan acetic acid aqueous solution.
[0023] Chitosan is a deacetylated form of the polysaccharide chitin, which is suitable for various soft materials, including aerogels. It is abundant in source, is a waste of some marine industries, is cheap, has good biocompatibility, and is soluble in weakly acidic solutions. It can easily react with many metal salts, such as Pd, Pt, Au, Ag, Ni, Co, etc., to form hydrogels under alkaline conditions, which can be used as aerogel precursors. When the biomass polysaccharide is chitosan, N atoms will be produced after calcination of chitosan. The present application can greatly promote substrate adsorption and ultimately enhance catalytic activity by additionally introducing heteroatoms such as N, P, S, B, and F.
[0024] In some embodiments, the metal salt is selected from one or more of chlorides, acetates, nitrates, or acetylacetonates containing Ni, Co, Mn, Cu, or Fe.
[0025] In some embodiments, the metal salt is selected from one or more of nickel chloride, nickel acetylacetonate, nickel acetate, nickel sulfate, nickel nitrate, ferric chloride, ferric nitrate, cobalt chloride, cobalt nitrate or cobalt acetylacetonate.
[0026] In some embodiments, the alkali solution containing heteroatoms is selected from one or more of an alkali solution containing N, an alkali solution containing P, an alkali solution containing S, an alkali solution containing B, or an alkali solution containing F.
[0027] In some embodiments, the alkali solution containing heteroatoms is selected from one or a combination of aqueous ammonia, sodium or potassium amide, sodium or potassium fluoride, sodium or potassium phosphate, disodium or potassium hydrogen phosphate, sodium or potassium dihydrogen phosphate, sodium or potassium borate, sodium or potassium hydrogen sulfate, sodium or potassium sulfite, and sodium or potassium pyrosulfate aqueous solution.
[0028] The alkali solution directly participates in the gel formation and is evenly dispersed in the entire gel network. Moreover, a series of heteroatom controllable doping can be achieved by adding alkali containing different heteroatoms and controlling their dosage. Therefore, hydrogels with uniform heteroatom distribution can be prepared by the alkali adjustment method.
[0029] In some embodiments, when the alkaline solution is ammonia water, the ammonia water can be heated by steam method to form ammonia gas, which is then combined with the metal-biomass polysaccharide acid solution in the form of alkaline gas molecules to form a hydrogel, and the N in the gel material is evenly distributed and has excellent gelling properties.
[0030] In some embodiments, the concentration of biomass polysaccharide in the acidic aqueous solution of biomass polysaccharide is 1-100 g / L, for example, 5 g / L, 20 g / L, 35 g / L, 50 g / L, 65 g / L, 80 g / L, 95 g / L.
[0031] In some embodiments, the concentration of the biomass polysaccharide in the acidic aqueous solution of biomass polysaccharide is 10-50 g / L.
[0032] In some embodiments, the concentration of biomass polysaccharides in the acidic aqueous solution of biomass polysaccharides is 20 g / L.
[0033] In some embodiments, the pH of the acidic aqueous solution is 0.1-5, for example, the pH is 0.1, 0.5, 1, 2, 3, 4, 5.
[0034] In some embodiments, the pH of the acidic aqueous solution is 0.5-2.
[0035] In some embodiments, the pH of the acidic aqueous solution is 1.
[0036] In some embodiments, the concentration of the metal salt in the metal salt aqueous solution is 1-100 g / L, for example, 5 g / L, 20 g / L, 35 g / L, 50 g / L, 65 g / L, 80 g / L, 95 g / L.
[0037] In some embodiments, the concentration of the alkali solution is 0.1-10 mol / L, for example, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L, 10 mol / L.
[0038] In some embodiments, the concentration of the alkali solution is 1-5 mol / L.
[0039] In some embodiments, the concentration of the alkali solution is 2 mol / L.
[0040] In some embodiments, the volume ratio of the alkali solution to the biomass polysaccharide-metal complex solution is 1:100-1:1, for example, 1:1, 1:2, 1:3, 1:4, 1:5, 1:10, 1:20, 1:30, 1:40, 1:50, 1:60, 1:70, or 1:90.
[0041] In some embodiments, the volume ratio of the alkali solution to the acidic aqueous solution of biomass polysaccharide is 1:1-1:15.
[0042] In some embodiments, the volume ratio of the alkali solution to the acidic aqueous solution of biomass polysaccharide is 1:10.
[0043] In some embodiments, the molar ratio of the metal element in the biomass polysaccharide-metal complex solution to the heteroatom in the alkali solution is 0.1-10:1, for example, 1:1, 3:1, 5:1, 7:1, 9:1, etc.
[0044] In some embodiments, the molar ratio of the metal element in the biomass polysaccharide-metal complex solution to the heteroatom in the alkali solution is 0.1-2:1, for example, 0.1:1, 0.5:1, 0.7:1, 1:1, 1.2:1, 1.5:1, 1.7:1, 2:1 or any value therebetween, preferably 0.8-1.2:1.
[0045] In some embodiments, the mass ratio of the biomass polysaccharide to the metal salt is 1-100:1, for example, 10:1, 30:1, 50:1, 70:1, 90:1, 100:1, etc.
[0046] In some embodiments, the mass ratio of the biomass polysaccharide to the metal salt is 1-10:1, for example, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1 or any value therebetween.
[0047] In some embodiments, before calcining, the hydrogel is first frozen to obtain a xerogel; and then the xerogel is freeze-dried.
[0048] In some embodiments, the hydrogel is frozen using a refrigerator.
[0049] In some embodiments, the freezing temperature is -30 to -90°C, for example, -35°C, -40°C, -45°C, -50°C, -55°C, -60°C, -65°C, -70°C, -75°C, -80°C, -85°C, or -90°C.
[0050] In some embodiments, the freezing temperature is -30 to -80°C.
[0051] In some embodiments, the freezing temperature is -80°C.
[0052] In some embodiments, the freezing method is gradient cooling, and the cooling rate of the freezing is 5-20°C / hour, for example, 5°C / hour, 7°C / hour, 9°C / hour, 11°C / hour, 13°C / hour, 15°C / hour, 17°C / hour, and 19°C / hour.
[0053] In some embodiments, the freezing method is gradient cooling, and the cooling rate of the freezing is 5-10°C / hour.
[0054] In some embodiments, the freezing method is gradient cooling, and the cooling rate of the freezing is 10°C / hour.
[0055] In some embodiments, the xerogel is freeze-dried using a freeze dryer.
[0056] In some embodiments, the freeze-drying temperature is -30 to -60°C, for example, -32°C, -34°C, -36°C, -38°C, -40°C, -42°C, -44°C, -46°C, -48°C, -50°C, -55°C, or -60°C.
[0057] In some embodiments, the freeze-drying temperature is -30 to -50°C.
[0058] In some embodiments, the freeze-drying temperature is -50°C.
[0059] In some embodiments, the lyophilization time is 6-36 hours, for example, 6 hours, 10 hours, 14 hours, 18 hours, 22 hours, 26 hours, 30 hours, or 34 hours.
[0060] In some embodiments, the lyophilization time is 10-15 hours.
[0061] In some embodiments, the lyophilization time is 12 hours.
[0062] In some embodiments, the calcining is performed in a tube furnace.
[0063] In some embodiments, the calcination atmosphere is a combination of one or more of argon, nitrogen, and hydrogen.
[0064] In some embodiments, the calcination atmosphere is nitrogen.
[0065] In some embodiments, the calcination temperature is 350-800°C, for example, 350°C, 400°C, 500°C, 600°C, 700°C, or 800°C.
[0066] In some embodiments, the calcination temperature is 350-500°C.
[0067] In some embodiments, the calcination temperature is 450°C.
[0068] In some embodiments, the calcination time is 1-3 hours, for example, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours or any value therebetween.
[0069] In some embodiments, the heating rate of the calcination is 1-5° C. / min.
[0070] In a third aspect, the present invention provides a use of the metal aerogel catalyst described in the first aspect of the present invention or the metal aerogel catalyst obtained by the preparation method described in the second aspect of the present invention in a selective hydrogenation reaction.
[0071] In some embodiments, the selective hydrogenation reaction is selected from the selective semi-hydrogenation of hydrolinalool, the selective semi-hydrogenation of diphenylacetylene, the selective hydrogenation of p-nitrostyrene, or the selective synthesis of azo reaction of nitrobenzene.
[0072] In some embodiments, the metal aerogel catalyst is directly used in the next round after being recovered by magnetic attraction without any additional activation step.
[0073] In a fourth aspect, the present invention provides a selective hydrogenation reaction of dehydrolinalool, wherein dehydrolinalool is used as a raw material and reacted with hydrogen in the presence of a catalyst and a solvent; wherein the catalyst comprises the metal aerogel catalyst described in the first aspect or the metal aerogel catalyst obtained by the preparation method described in the second aspect.
[0074] In some embodiments, the reaction temperature is 50-90°C, such as 50°C, 60°C, 70°C, 80°C, 90°C or any value therebetween, preferably 60-80°C.
[0075] In some embodiments, the reaction temperature is 70°C.
[0076] In some embodiments, the reaction pressure is 2-10 atmospheres, for example, 2 atmospheres, 3 atmospheres, 4 atmospheres, 5 atmospheres, 6 atmospheres, 7 atmospheres, 8 atmospheres, 9 atmospheres, 10 atmospheres or any value therebetween, preferably 10 atmospheres.
[0077] In some embodiments, the reaction time is 5-20 hours, for example, 5 hours, 7 hours, 9 hours, 11 hours, 13 hours, 15 hours, 17 hours, 19 hours or any value therebetween, preferably 5-10 hours.
[0078] In some embodiments, the reaction time is 9 hours.
[0079] In some embodiments, the solvent is ethanol.
[0080] The preparation method of the heteroatom-doped carbon-coated cheap metal catalytic material based on hydrogel derivation provided by the present invention is to dissolve a certain amount of chitosan in an acidic aqueous solution, stir for a certain period of time, and then introduce an alkali solution containing different heteroatoms to form a hydrogel. The hydrogel is placed in a refrigerator for freezing, taken out and freeze-dried in a freeze dryer, and then calcined in a specific atmosphere to obtain a series of heteroatom-doped carbon-coated cheap metal aerogel catalytic materials.
[0081] In the present invention, the acidic aqueous solution of chitosan is one of chitosan formic acid aqueous solution, acetic acid aqueous solution, propionic acid aqueous solution, hydrochloric acid aqueous solution, sulfuric acid aqueous solution, phosphoric acid aqueous solution, and nitric acid aqueous solution, preferably chitosan acetic acid aqueous solution;
[0082] In the present invention, the chitosan concentration used is 1-100 g / L, preferably 20 g / L, and the pH of the acid solution is 1-5, preferably 1;
[0083] In the present invention, the hydrogel is formed by passing an alkali solution into a chitosan acid solution, wherein the alkali solution is one or a combination of aqueous ammonia, sodium or potassium amide, sodium or potassium fluoride, sodium or potassium phosphate, disodium or potassium hydrogen phosphate, sodium or potassium dihydrogen phosphate, sodium or potassium borate, sodium or potassium hydrogen sulfate, sodium or potassium sulfite, sodium or potassium pyrosulfate aqueous solution, and by changing the type of heteroatoms in the alkali anion used, doping of heteroatoms such as N, P, B, S, and F can be easily achieved;
[0084] The concentration of the alkali solution used in the present invention is 0.1-10 mol / L, preferably 2 mol / L, and the dosage ratio of the alkali solution to the chitosan acid solution is 1:100-1:1, preferably 1:10;
[0085] In the present invention, when the alkaline solution used is ammonia water, the ammonia water can be heated by steam method to form ammonia gas, and then the alkaline gas molecules form a hydrogel with the metal-chitosan acid solution. The N in the gel material is evenly distributed and the gelling performance is excellent.
[0086] In the present invention, the obtained hydrogel is placed in a refrigerator and frozen at a temperature of -30--80°C, preferably -80°C, and the freezing method is a gradient cooling method, from room temperature to the desired temperature at a rate of 5-20°C / hour, preferably 10°C / hour;
[0087] In the present invention, the frozen xerogel is freeze-dried in a freeze dryer, the freeze-drying temperature is -30--50°C, preferably -50°C, and the freeze-drying time is 6-36 hours, preferably 12 hours.
[0088] In the present invention, the xerogel formed after freeze-drying is placed in a tubular furnace, the gas atmosphere is one or a combination of argon, nitrogen, and hydrogen, preferably nitrogen, and the calcination temperature is 350-800°C, preferably 450°C.
[0089] In the present invention, after obtaining the heteroatom-doped aerogel catalytic material, it is applied to the selective semi-hydrogenation of dehydrolinalool, the selective semi-hydrogenation of diphenylacetylene, the selective hydrogenation of p-nitrostyrene, and the selective synthesis of azo from nitrobenzene to investigate its catalytic performance and stable recycling performance, the reaction temperature is 70°C, the hydrogen pressure is 10 atmospheres, the reaction solvent is ethanol, and the reaction time is 9 hours. After the catalyst is recovered by magnetic attraction, it directly enters the next round of application without any additional activation step.
[0090] Compared with the prior art, the present invention has the following beneficial effects:
[0091] The present invention uses biomass polysaccharides and common cheap metal salts to prepare metal-chitosan hydrogels under the action of alkali, and by adjusting the type of heteroatoms in the alkali and the amount of the alkali, a series of carbon-coated cheap metal aerogel catalysts doped with different heteroatoms, such as N, P, B, S, and F, are realized. The activity of the catalytic material is improved by utilizing the modification of the carbon material by heteroatoms and the enhanced electron transport properties with the active metal center. At the same time, the type and content of heteroatoms are controlled to adjust the catalytic microstructure of the active metal center, and the selectivity of the material in the hydrogenation reaction is improved. The catalyst has the advantages of uniform heteroatom distribution, clear structure, and easy regulation, so that the coordinated active metal center is highly dispersed. The catalyst is used in reactions such as selective hydrogenation, which are widely used in industry, and it shows excellent catalytic performance, and the activity and selectivity of the material can be regulated by simply adjusting the type and amount of alkali in the hydrogel formation process, which is conducive to further industrial application.
[0092] The method of the present invention is simple, has wide universality, good doping effect, and is adjustable and controllable. The prepared metal aerogel catalyst has a wide range of applications, and does not require the addition of additional dopants or complex organic synthesis. Various heteroatoms such as N, P, B, S, and F can be doped by the method. The heteroatoms are evenly distributed and easy to control, and the catalytic center microstructure of the obtained material can be finely controlled to improve its catalytic activity and selectivity. On the other hand, the anchoring effect of heteroatoms on metals is used to improve the stability of the material, so that it exhibits high efficiency in a series of selective hydrogenation reactions, and has broad industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0093] Figure 1 (a) is the catalyst Ni obtained in Example 9 0.25 @B2C-400 powder PXRD analysis results;
[0094] Figure 1 (b) is the catalyst Ni obtained in Example 8 0.25 @S2C-400 powder PXRD analysis results;
[0095] Figure 1 (c) is the catalyst Ni obtained in Example 6 0.25 Powder PXRD analysis results of @P2C-400;
[0096] Figure 1 (d) is a graph showing the Ramen analysis results of the catalysts obtained in Examples 6, 8 and 9;
[0097] Figure 2 The catalyst Ni obtained in Example 1 0.25 @N2C-400 X-ray photoelectron spectroscopy (XPS) analysis results. DETAILED DESCRIPTION
[0098] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments and drawings. The specific embodiments described herein are only used to explain the present invention and are not intended to constitute any limitation to the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concepts of the present disclosure. Such structures and technologies are also described in many publications.
[0099] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0100] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the raw materials, instruments and equipment used in the following examples, etc., can all be purchased on the market or can be obtained by existing methods; the reagent amounts, unless otherwise specified, are the reagent amounts used in conventional experimental operations; the experimental methods, unless otherwise specified, are all conventional methods.
[0101] The room temperature in the present invention refers to 20-30°C.
[0102] Example 1: N-doped Ni-based metal aerogel catalyst Ni 0.25 Preparation of @N2C-400:
[0103] Chitosan (1.0 g), water (50 mL) and 0.5 mL of glacial acetic acid were added to a 100 mL round-bottom flask equipped with a magnetic device. The mixture was stirred at room temperature for two hours until the chitosan was completely dissolved to obtain an acidic chitosan aqueous solution with a pH of 1. NiCl2·6H2O (250 mg) was dissolved in 4 mL of water to obtain an aqueous solution of nickel salt. The aqueous solution of nickel salt was slowly added dropwise to the acidic chitosan aqueous solution with a pH of 1. The resulting reaction system was stirred overnight at room temperature to obtain a synthetic chitosan-Ni complex solution. 5 mL of the chitosan-Ni complex solution was taken into a 20 mL sample bottle equipped with a magnetic device. 0.5 mL of 2 mol / L NaNH2 solution was slowly added dropwise under vigorous stirring. After the hydrogel was formed, the stirring was stopped. The resulting hydrogel was frozen to -80°C at a rate of 10°C / hour, taken out and placed in a freeze dryer at -50°C for lyophilization for 12 hours. The obtained powder was placed in a graphite boat and subjected to high temperature pyrolysis in a tube furnace in a nitrogen atmosphere. The pyrolysis temperature program was to increase the temperature from room temperature to 400°C at a rate of 2°C per minute and maintain it at 400°C for 2 hours. When the pyrolysis temperature was 400°C, the obtained material was marked as Ni 0.25 @N2C-400, N atoms account for 4.85% of the total mass of the catalyst. The XPS of the catalyst is as follows Figure 2 shown.
[0104] Example 2: N-doped Ni-based metal aerogel catalyst Ni 0.5 Preparation of @N2C-400:
[0105] Chitosan (1.0 g), water (50 mL) and 0.5 mL of glacial acetic acid were added to a 100 mL round-bottom flask equipped with a magnetic device. The mixture was stirred at room temperature for two hours until the chitosan was completely dissolved to obtain an acidic chitosan aqueous solution with a pH of 1. NiCl2·6H2O (500 mg) was dissolved in 4 mL of water to obtain an aqueous solution of nickel salt. The aqueous solution of nickel salt was slowly added dropwise to the acidic chitosan aqueous solution. The resulting reaction system was stirred overnight at room temperature to obtain a synthetic chitosan-Ni complex solution. 5 mL of the chitosan-Ni complex solution was taken into a 20 mL sample bottle equipped with a magnetic device. 0.5 mL of 2 mol / L NaNH2 solution was slowly added dropwise under vigorous stirring. After that, a hydrogel was formed and stirring was stopped. The resulting hydrogel was frozen to -80°C at a rate of 10°C / hour and then taken out and freeze-dried in a freeze dryer at -50°C for 12 hours. The obtained powder was placed in a graphite boat and subjected to high temperature pyrolysis in a tube furnace in a nitrogen atmosphere. The pyrolysis temperature program was to increase the temperature from room temperature to 400°C at a rate of 2°C per minute and maintain it at 400°C for 2 hours. When the pyrolysis temperature was 400°C, the obtained material was marked as Ni 0.5 @N2C-400.
[0106] Example 3: N-doped Ni-based metal aerogel catalyst Ni 0.1 Preparation of @N2C-400:
[0107] Chitosan (1.0 g), water (50 mL) and 0.5 mL of glacial acetic acid were added to a 100 mL round-bottom flask equipped with a magnetic device. The mixture was stirred at room temperature for two hours until the chitosan was completely dissolved to obtain an acidic chitosan aqueous solution with a pH of 1. NiCl2·6H2O (100 mg) was dissolved in 4 mL of water to obtain an aqueous solution of nickel salt. The aqueous solution of nickel salt was slowly added dropwise to the acidic chitosan aqueous solution. The resulting reaction system was stirred overnight at room temperature to obtain a synthetic chitosan-Ni complex solution. 5 mL of the chitosan-Ni complex solution was taken into a 20 mL sample bottle equipped with a magnetic device. 0.5 mL of 2 mol / L NaNH2 solution was slowly added dropwise under vigorous stirring. After that, a hydrogel was formed and stirring was stopped. The resulting hydrogel was frozen to -80°C at a rate of 10°C / hour and then taken out and freeze-dried in a freeze dryer at -50°C for 12 hours. The obtained powder was placed in a graphite boat and subjected to high temperature pyrolysis in a tube furnace in a nitrogen atmosphere. The pyrolysis temperature program was to increase the temperature from room temperature to 400°C at a rate of 2°C per minute and maintain it at 400°C for 2 hours. When the pyrolysis temperature was 400°C, the obtained material was marked as Ni 0.1 @N2C-400.
[0108] Example 4: N-doped Ni-based metal aerogel catalyst Ni 0.25Preparation of @N1C-400:
[0109] Chitosan (1.0 g), water (50 mL) and 0.5 mL of glacial acetic acid were added to a 100 mL round-bottom flask equipped with a magnetic device. The mixture was stirred at room temperature for two hours until the chitosan was completely dissolved to obtain an acidic chitosan aqueous solution with a pH of 1. NiCl2·6H2O (250 mg) was dissolved in 4 mL of water to obtain an aqueous solution of nickel salt. The aqueous solution of nickel salt was slowly added dropwise to the acidic chitosan aqueous solution. The resulting reaction system was stirred overnight at room temperature to obtain a synthetic chitosan-Ni complex solution. 5 mL of the chitosan-Ni complex solution was taken into a 20 mL sample bottle equipped with a magnetic device. 0.5 mL of 1 mol / L NaNH2 solution was slowly added dropwise under vigorous stirring. After that, a hydrogel was formed and stirring was stopped. The resulting hydrogel was frozen to -80°C at a rate of 10°C / hour and then taken out and freeze-dried in a freeze dryer at -50°C for 12 hours. The obtained powder was placed in a graphite boat and subjected to high temperature pyrolysis in a tube furnace in a nitrogen atmosphere. The pyrolysis temperature program was to increase the temperature from room temperature to 400°C at a rate of 2°C per minute and maintain it at 400°C for 2 hours. When the pyrolysis temperature was 400°C, the obtained material was marked as Ni 0.25 @N1C-400.
[0110] Example 5: N-doped Ni-based metal aerogel catalyst Ni 0.25 @N 10 Preparation of C-400:
[0111] Chitosan (1.0 g), water (50 mL) and 0.5 mL of glacial acetic acid were added to a 100 mL round-bottom flask equipped with a magnetic device. The mixture was stirred at room temperature for two hours until the chitosan was completely dissolved to obtain an acidic chitosan aqueous solution with a pH of 1. NiCl2·6H2O (250 mg) was dissolved in 4 mL of water to obtain an aqueous solution of nickel salt. The aqueous solution of nickel salt was slowly added dropwise to the acidic chitosan aqueous solution. The resulting reaction system was stirred overnight at room temperature to obtain a synthetic chitosan-Ni complex solution. 5 mL of the chitosan-Ni complex solution was taken into a 20 mL sample bottle equipped with a magnetic device. 0.5 mL of 10 mol / L NaNH2 solution was slowly added dropwise under vigorous stirring. After that, a hydrogel was formed and stirring was stopped. The resulting hydrogel was frozen to -80°C at a rate of 10°C / hour and then taken out and freeze-dried in a freeze dryer at -50°C for 12 hours. The obtained powder was placed in a graphite boat and subjected to high temperature pyrolysis in a tube furnace in a nitrogen atmosphere. The pyrolysis temperature program was to increase the temperature from room temperature to 400°C at a rate of 2°C per minute and maintain it at 400°C for 2 hours. When the pyrolysis temperature was 400°C, the obtained material was marked as Ni 0.25 @N 10 C-400.
[0112] Example 6: P-doped Ni-based metal aerogel catalyst Ni 0.25 Preparation of @P2C-400:
[0113] Chitosan (1.0 g), water (50 mL) and 0.5 mL of glacial acetic acid were added to a 100 mL round-bottom flask equipped with a magnetic device. The mixture was stirred at room temperature for two hours until the chitosan was completely dissolved to obtain an acidic chitosan aqueous solution with a pH of 1. NiCl2·6H2O (250 mg) was dissolved in 4 mL of water to obtain an aqueous solution of nickel salt. The aqueous solution of nickel salt was slowly added dropwise to the acidic chitosan aqueous solution. The resulting reaction system was stirred overnight at room temperature to obtain a synthetic chitosan-Ni complex solution. 5 mL of the chitosan-Ni complex solution was taken into a 20 mL sample bottle equipped with a magnetic device. 0.5 mL of 2 mol / L NaH2PO4 solution was slowly added dropwise under vigorous stirring. After that, a hydrogel was formed and stirring was stopped. The resulting hydrogel was frozen to -80°C at a rate of 10°C / hour and then taken out and freeze-dried in a freeze dryer at -50°C for 12 hours. The obtained powder was placed in a graphite boat and subjected to high temperature pyrolysis in a tube furnace in a nitrogen atmosphere. The pyrolysis temperature program was to increase the temperature from room temperature to 400°C at a rate of 2°C per minute and maintain it at 400°C for 2 hours. When the pyrolysis temperature was 400°C, the obtained material was marked as Ni 0.25 @P2C-400. The PXRD pattern of the catalyst is as follows Figure 1 As shown in (c), the active phase is Ni.
[0114] Example 7: F-doped Ni-based metal aerogel catalyst Ni 0.25 @F2C-400 preparation:
[0115] Chitosan (1.0 g), water (50 mL) and 0.5 mL of glacial acetic acid were added to a 100 mL round-bottom flask equipped with a magnetic device. The mixture was stirred at room temperature for two hours until the chitosan was completely dissolved to obtain an acidic chitosan aqueous solution with a pH of 1. NiCl2·6H2O (250 mg) was dissolved in 4 mL of water to obtain an aqueous solution of nickel salt. The aqueous solution of nickel salt was slowly added dropwise to the acidic chitosan aqueous solution. The resulting reaction system was stirred overnight at room temperature to obtain a synthetic chitosan-Ni complex solution. 5 mL of the chitosan-Ni complex solution was taken into a 20 mL sample bottle equipped with a magnetic device. 0.5 mL of 2 mol / L NaF solution was slowly added dropwise under vigorous stirring. After that, a hydrogel was formed and stirring was stopped. The resulting hydrogel was frozen to -80°C at a rate of 10°C / hour and then taken out and freeze-dried in a freeze dryer at -50°C for 12 hours. The obtained powder was placed in a graphite boat and subjected to high temperature pyrolysis in a tube furnace in a nitrogen atmosphere. The pyrolysis temperature program was to increase the temperature from room temperature to 400°C at a rate of 2°C per minute and maintain it at 400°C for 2 hours. When the pyrolysis temperature was 400°C, the obtained material was marked as Ni0.25 @F2C-400.
[0116] Example 8: S-doped Ni-based metal aerogel catalyst Ni 0.25 @S2C-400 preparation:
[0117] Chitosan (1.0 g), water (50 mL) and 0.5 mL of glacial acetic acid were added to a 100 mL round-bottom flask equipped with a magnetic device. The mixture was stirred at room temperature for two hours until the chitosan was completely dissolved to obtain an acidic chitosan aqueous solution with a pH of 1. NiCl2·6H2O (250 mg) was dissolved in 4 mL of water to obtain an aqueous solution of nickel salt. The aqueous solution of nickel salt was slowly added dropwise to the acidic chitosan aqueous solution. The resulting reaction system was stirred overnight at room temperature to obtain a synthetic chitosan-Ni complex solution. 5 mL of the chitosan-Ni complex solution was taken into a 20 mL sample bottle equipped with a magnetic device. 0.5 mL of 2 mol / L NaHSO4 solution was slowly added dropwise under vigorous stirring. After that, a hydrogel was formed and stirring was stopped. The resulting hydrogel was frozen to -80°C at a rate of 10°C / hour and then taken out and freeze-dried in a freeze dryer at -50°C for 12 hours. The obtained powder was placed in a graphite boat and subjected to high temperature pyrolysis in a tube furnace in a nitrogen atmosphere. The pyrolysis temperature program was to increase the temperature from room temperature to 400°C at a rate of 2°C per minute and maintain it at 400°C for 2 hours. When the pyrolysis temperature was 400°C, the obtained material was marked as Ni 0.25 @S2C-400. The PXRD pattern of the catalyst is as follows Figure 1 As shown in (b), the active phase is Ni3S2.
[0118] Example 9: B-doped Ni-based metal aerogel catalyst Ni 0.25 @B2C-400 preparation:
[0119] Chitosan (1.0 g), water (50 mL) and 0.5 mL of glacial acetic acid were added to a 100 mL round-bottom flask equipped with a magnetic device. The mixture was stirred at room temperature for two hours until the chitosan was completely dissolved to obtain an acidic chitosan aqueous solution with a pH of 1. NiCl2·6H2O (250 mg) was dissolved in 4 mL of water to obtain an aqueous solution of nickel salt. The aqueous solution of nickel salt was slowly added dropwise to the acidic chitosan aqueous solution. The resulting reaction system was stirred overnight at room temperature to obtain a synthetic chitosan-Ni complex solution. 5 mL of the chitosan-Ni complex solution was taken into a 20 mL sample bottle equipped with a magnetic device. 0.5 mL of 2 mol / L sodium borate solution was slowly added dropwise under vigorous stirring. After that, a hydrogel was formed and stirring was stopped. The resulting hydrogel was frozen to -80°C at a rate of 10°C / hour and then taken out and freeze-dried in a freeze dryer at -50°C for 12 hours. The obtained powder was placed in a graphite boat and subjected to high temperature pyrolysis in a tube furnace in a nitrogen atmosphere. The pyrolysis temperature program was to increase the temperature from room temperature to 400°C at a rate of 2°C per minute and maintain it at 400°C for 2 hours. When the pyrolysis temperature was 400°C, the obtained material was marked as Ni 0.25 @B2C-400. The PXRD pattern of the catalyst is as follows Figure 1 (a) shows that the active phase is Ni. The Ramen analysis results of the catalysts obtained in Examples 6, 8 and 9 are shown in FIG. Figure 1 (d) as shown.
[0120] Example 10
[0121] Chitosan (1.0 g), water (50 mL) and 0.5 mL of glacial acetic acid were added to a 100 mL round-bottom flask equipped with a magnetic device. The mixture was stirred at room temperature for two hours until the chitosan was completely dissolved to obtain an acidic chitosan aqueous solution with a pH of 1. NiCl2·6H2O (500 mg) was dissolved in 4 mL of water to obtain an aqueous solution of nickel salt. The aqueous solution of nickel salt was slowly added dropwise to the acidic chitosan aqueous solution. The resulting reaction system was stirred overnight at room temperature to obtain a synthetic chitosan-Ni complex solution. 5 mL of the chitosan-Ni complex solution was taken into a 20 mL sample bottle equipped with a magnetic device. 0.5 mL of 2 mol / L NaH2PO4 solution was slowly added dropwise under vigorous stirring. After that, a hydrogel was formed and stirring was stopped. The resulting hydrogel was frozen to -80°C at a rate of 10°C / hour and then taken out and freeze-dried in a freeze dryer at -50°C for 12 hours. The obtained powder was placed in a graphite boat and subjected to high temperature pyrolysis in a tube furnace in a nitrogen atmosphere. The pyrolysis temperature program was to increase the temperature from room temperature to 400°C at a rate of 2°C per minute and maintain it at 400°C for 2 hours. When the pyrolysis temperature was 400°C, the obtained material was marked as Ni 0.5 @P2C-400.
[0122] Embodiment 11
[0123] Chitosan (1.0 g), water (50 mL) and 0.5 mL of glacial acetic acid were added to a 100 mL round-bottom flask equipped with a magnetic device. The mixture was stirred at room temperature for two hours until the chitosan was completely dissolved to obtain an acidic chitosan aqueous solution with a pH of 1. NiCl2·6H2O (100 mg) was dissolved in 4 mL of water to obtain an aqueous solution of nickel salt. The aqueous solution of nickel salt was slowly added dropwise to the acidic chitosan aqueous solution. The resulting reaction system was stirred overnight at room temperature to obtain a synthetic chitosan-Ni complex solution. 5 mL of the chitosan-Ni complex solution was taken into a 20 mL sample bottle equipped with a magnetic device. 0.5 mL of 2 mol / L NaH2PO4 solution was slowly added dropwise under vigorous stirring. After that, a hydrogel was formed and stirring was stopped. The resulting hydrogel was frozen to -80°C at a rate of 10°C / hour and then taken out and freeze-dried in a freeze dryer at -50°C for 12 hours. The obtained powder was placed in a graphite boat and subjected to high temperature pyrolysis in a tube furnace in a nitrogen atmosphere. The pyrolysis temperature program was to increase the temperature from room temperature to 400°C at a rate of 2°C per minute and maintain it at 400°C for 2 hours. When the pyrolysis temperature was 400°C, the obtained material was marked as Ni 0.1 @P2C-400.
[0124] Example 12
[0125] Chitosan (1.0 g), water (50 mL) and 0.5 mL of glacial acetic acid were added to a 100 mL round-bottom flask equipped with a magnetic device. The mixture was stirred at room temperature for two hours until the chitosan was completely dissolved to obtain an acidic chitosan aqueous solution with a pH of 1. NiCl2·6H2O (250 mg) was dissolved in 4 mL of water to obtain an aqueous solution of nickel salt. The aqueous solution of nickel salt was slowly added dropwise to the acidic chitosan aqueous solution. The resulting reaction system was stirred overnight at room temperature to obtain a synthetic chitosan-Ni complex solution. 5 mL of the chitosan-Ni complex solution was taken into a 20 mL sample bottle equipped with a magnetic device. 0.5 mL of 1 mol / L NaH2PO4 solution was slowly added dropwise under vigorous stirring. After that, a hydrogel was formed and stirring was stopped. The resulting hydrogel was frozen to -80°C at a rate of 10°C / hour and then taken out and freeze-dried in a freeze dryer at -50°C for 12 hours. The obtained powder was placed in a graphite boat and subjected to high temperature pyrolysis in a tube furnace in a nitrogen atmosphere. The pyrolysis temperature program was to increase the temperature from room temperature to 400°C at a rate of 2°C per minute and maintain it at 400°C for 2 hours. When the pyrolysis temperature was 400°C, the obtained material was marked as Ni 0.25 @P1C-400.
[0126] Embodiment 13
[0127] Chitosan (1.0 g), water (50 mL) and 0.5 mL of glacial acetic acid were added to a 100 mL round-bottom flask equipped with a magnetic device. The mixture was stirred at room temperature for two hours until the chitosan was completely dissolved to obtain an acidic chitosan aqueous solution with a pH of 1. NiCl2·6H2O (250 mg) was dissolved in 4 mL of water to obtain an aqueous solution of nickel salt. The aqueous solution of nickel salt was slowly added dropwise to the acidic chitosan aqueous solution. The resulting reaction system was stirred overnight at room temperature to obtain a synthetic chitosan-Ni complex solution. 5 mL of the chitosan-Ni complex solution was taken into a 20 mL sample bottle equipped with a magnetic device. 0.5 mL of 10 mol / L NaH2PO4 solution was slowly added dropwise under vigorous stirring. After that, a hydrogel was formed and stirring was stopped. The resulting hydrogel was frozen to -80°C at a rate of 10°C / hour and then taken out and freeze-dried in a freeze dryer at -50°C for 12 hours. The obtained powder was placed in a graphite boat and subjected to high temperature pyrolysis in a tube furnace in a nitrogen atmosphere. The pyrolysis temperature program was to increase the temperature from room temperature to 400°C at a rate of 2°C per minute and maintain it at 400°C for 2 hours. When the pyrolysis temperature was 400°C, the obtained material was marked as Ni 0.25 @P 10 C-400.
[0128] Comparative Example 1
[0129] Chitosan (1.0 g), water (50 mL) and 0.5 mL of glacial acetic acid were added to a 100 mL round-bottom flask equipped with a magnetic device, and then 0.5 mL of glacial acetic acid was added. The mixture was stirred at room temperature for two hours until the chitosan was completely dissolved. NiCl2·6H2O (250 mg) was dissolved in 4 mL of water, and the aqueous solution of nickel salt was slowly added to the acidic chitosan aqueous solution. The resulting reaction system was stirred overnight at room temperature to obtain a synthetic chitosan-Ni complex solution. 5 mL of the chitosan-Ni complex solution was taken into a 20 mL sample bottle equipped with a magnetic device, and 0.5 mL of 2 mol / L NaOH solution was slowly added under vigorous stirring. After the hydrogel was formed, the stirring was stopped. The resulting hydrogel was frozen to -80°C at a rate of 10°C / hour, and then taken out and placed in a freeze dryer at -50°C for lyophilization for 12 hours. The obtained powder was placed in a graphite boat and subjected to high temperature pyrolysis in a tube furnace in a nitrogen atmosphere. The pyrolysis temperature program was to increase the temperature from room temperature to 400°C at a rate of 2°C per minute and maintain it at 400°C for 2 hours. When the pyrolysis temperature was 400°C, the obtained material was marked as Ni 0.25 @C-400.
[0130] Application Example 1: Effects of different heteroatom-doped metal aerogel catalysts in the synthesis of linalool:
[0131] Dehydrolinalool (2mmol, 304mg), ethanol (10mL), water (4mL) and the metal aerogel catalyst prepared in Examples 1, 6-13 or the catalyst prepared in Comparative Example 1 were added to a tetrafluoroethylene liner equipped with a magnetic stirrer, and then the liner was placed in an autoclave and the autoclave was tightened. After the autoclave was purged with hydrogen three times, 10 atmospheres of hydrogen were filled, and then the autoclave was placed in a 70°C oil bath and stirred for 9 hours. After the reaction was complete, the autoclave was cooled to room temperature and the pressure was slowly released. The reaction yield was determined by GC and accurately determined by the area normalization method. The results are shown in Table 1.
[0132] Table 1 Effects of different heteroatom-doped metal aerogel catalysts in the synthesis of linalool
[0133]
[0134]
[0135] As can be seen from Table 1, heteroatoms have a great influence on the reaction. Due to its strong coordination ability and strong electron donating effect, P has better catalytic performance than N-doped aerogel materials, and the selectivity has increased by nearly 10%, which proves the feasibility of this strategy. S has a poisoning effect on the metal center, resulting in a decrease in the activity of the obtained material, with only a 50% conversion rate. However, because S poisons the metal center, its hydrogenation selectivity is further enhanced, and the highest linalool selectivity (96%) can be obtained. B and F doping do not significantly improve the selectivity of the material, and its doping effect is general. In summary, the catalytic material doped with P can achieve the highest yield in the production of linalool. In industrial production, product purification is a very important link, so it is necessary to further improve the selectivity of P-doped materials. By changing the metal content and P content, the selectivity can be increased to 94%.
[0136] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A metal aerogel catalyst, comprising a metal aerogel and heteroatoms doped in the metal aerogel; the metal aerogel comprises a metal and a carbon material coated on the metal; optionally, the carbon material comprises N; in, The metal is selected from one or more of Ni, Co, Mn, Cu or Fe; The heteroatom is selected from one or more of N, P, S, B or F, preferably S and / or P; and / or The total amount of the heteroatoms and N in the carbon material accounts for 0.5-15% of the mass of the metal aerogel catalyst; Preferably, the heteroatoms account for 0.5-6% of the mass of the metal aerogel catalyst; Preferably, the total amount of N in the carbon material accounts for 1-10% of the mass of the metal aerogel catalyst; Preferably, the metal accounts for 1-10% of the mass of the metal aerogel catalyst; The carbon material includes carbon-containing substances formed by calcining biomass polysaccharides; preferably, the biomass polysaccharides are selected from one or more of chitosan, sodium alginate, glucose, bacterial cellulose, agarose or hyaluronic acid.
2. A method for preparing a metal aerogel catalyst, comprising the following steps: (1) mixing an acidic aqueous solution containing biomass polysaccharides, a metal salt aqueous solution and an alkaline solution containing heteroatoms to form a hydrogel; (2) calcining the hydrogel to obtain a metal aerogel catalyst; Preferably, the method for preparing the hydrogel comprises: S1, mixing an acidic aqueous solution containing biomass polysaccharides with an aqueous solution of metal salts to obtain a biomass polysaccharide-metal complex solution; S2, adding an alkali solution containing heteroatoms dropwise into the polysaccharide-metal complex solution to obtain a hydrogel.
3. The preparation method according to claim 2, characterized in that: The biomass polysaccharide is selected from one or more of chitosan, sodium alginate, glucose, bacterial cellulose, agarose or hyaluronic acid; and / or The acidic aqueous solution is selected from one or more of an aqueous formic acid solution, an aqueous acetic acid solution, an aqueous propionic acid solution, an aqueous hydrochloric acid solution, an aqueous sulfuric acid solution, an aqueous phosphoric acid solution or an aqueous nitric acid solution; and / or The metal salt is selected from one or more of chlorides, acetates, nitrates or acetylacetonates containing Ni, Co, Mn, Cu or Fe; Preferably, the metal salt is selected from one or more of nickel chloride, nickel acetylacetonate, nickel acetate, nickel sulfate, nickel nitrate, ferric chloride, ferric nitrate, cobalt chloride, cobalt nitrate or cobalt acetylacetonate; and / or The alkali solution containing heteroatoms is selected from one or more of an alkali solution containing N, an alkali solution containing P, an alkali solution containing S, an alkali solution containing B or an alkali solution containing F; Preferably, the alkali solution containing heteroatoms is selected from one or a combination of aqueous ammonia, sodium or potassium amide, sodium or potassium fluoride, sodium or potassium phosphate, disodium or potassium hydrogen phosphate, sodium or potassium dihydrogen phosphate, sodium or potassium borate, sodium or potassium hydrogen sulfate, sodium or potassium sulfite, sodium or potassium pyrosulfate aqueous solution.
4. The preparation method according to claim 2 or 3, characterized in that: The concentration of the biomass polysaccharide in the acidic aqueous solution of the biomass polysaccharide is 1-100 g / L, preferably 10-50 g / L; and / or The pH of the acidic aqueous solution is 0.1-5, preferably 0.5-2; and / or The concentration of the metal salt in the metal salt aqueous solution is 1-100 g / L.
5. The preparation method according to any one of claims 2 to 4, characterized in that: The concentration of the alkali solution is 0.1-10 mol / L, preferably 1-5 mol / L; and / or The volume ratio of the alkali solution to the biomass polysaccharide-metal complex solution is 1:100-1:1, preferably 1:1-1:15; and / or the mass ratio of the metal salt aqueous solution to the biomass polysaccharide acidic aqueous solution is 1:5-1:50; and / or The molar ratio of the metal element in the biomass polysaccharide-metal complex solution to the heteroatom in the alkali solution is 0.1-10:1, preferably 0.1-2:1, more preferably 0.8-1.2:1; and / or The mass ratio of the biomass polysaccharide to the metal salt is 1-100:1, preferably 1-10:
1.
6. The preparation method according to any one of claims 2 to 5, characterized in that: Before calcining, the hydrogel is firstly frozen to obtain a xerogel; and the xerogel is then freeze-dried; Preferably, the hydrogel is frozen in a refrigerator. Preferably, the freezing temperature is -30 to -90°C, preferably -30 to -80°C. Preferably, the freezing method is gradient cooling, and the freezing cooling rate is 5-20°C / hour, preferably 5-10°C / hour.
7. The preparation method according to claim 6, characterized in that: The xerogel is freeze-dried using a freeze dryer. Preferably, the freeze-drying temperature is -30 to -60°C, preferably -30 to -50°C; and / or the freeze-drying time is 6 to 36 hours, preferably 10 to 15 hours.
8. The preparation method according to any one of claims 2 to 7, characterized in that: The calcination is carried out in a tube furnace, and / or The calcination atmosphere is a combination of one or more of argon, nitrogen and hydrogen; and / or The calcination temperature is 350-800°C, preferably 350-500°C; and / or The calcination time is 1-3 hours. Preferably, the heating rate of the calcination is 1-5°C / min.
9. Use of the metal aerogel catalyst according to claim 1 or the metal aerogel catalyst obtained by the preparation method according to any one of claims 2 to 8 in a selective hydrogenation reaction; Preferably, the selective hydrogenation reaction is selected from the group consisting of selective semi-hydrogenation of dehydrolinalool, selective semi-hydrogenation of diphenylacetylene, selective hydrogenation of p-nitrostyrene or selective azo synthesis reaction of nitrobenzene.
10. A selective hydrogenation reaction of dehydrolinalool, taking dehydrolinalool as a raw material, reacting with hydrogen in the presence of a catalyst and a solvent; wherein: The catalyst comprises the metal aerogel catalyst according to claim 1 or the metal aerogel catalyst obtained by the preparation method according to any one of claims 2 to 8; Preferably, the reaction temperature is 50-90°C, preferably 60-80°C; and / or The reaction pressure is 2-10 atmospheres, preferably 10 atmospheres; and / or The reaction time is 5-20 hours, preferably 5-10 hours; and / or The solvent is ethanol.
Citation Information
Patent Citations
Preparation method of sulfonic acid functionalized N, P and B co-doped carbon material uranium electro-adsorbent
CN116715327A
Doped porous hard carbon composite material and preparation method and application thereof
CN116826024A
Method for preparing heteroatom-doped nickel-rich material through high shear reaction and application of heteroatom-doped nickel-rich material in battery positive electrode
CN116854150A
Selective hydrogenation catalyst for unsaturated ketone and preparation method and application thereof
CN108940346A
Sulfur-doped carbon-coated nickel catalyst as well as preparation method and application thereof
CN115138377A